Public health measures during an anticipated influenza pandemic: Factors influencing willingness to comply - Melanie Taylor; Beverley Raphael; Margo Barr; Kingsley Agho; Garry Stevens; Louisa Jorm (Dove Medical Press, 2009)
Melanie Taylor1, Beverley Raphael1, Margo Barr2, Kingsley Agho1, Garry Stevens1, Louisa Jorm11School of Medicine, University of Western Sydney, Sydney, Australia; 2Centre for Epidemiology and Research, New South Wales Department of Health, Sydney, AustraliaAbstract: This research assessed factors associated with willingness to comply with vaccination, isolation, and face mask wearing during an anticipated influenza pandemic. Data were collected from 2081 adults (16+) using a module of questions incorporated into the NSW Health Adult Population Health Survey. High levels of willingness to comply were reported with 73% either very or extremely willing to receive vaccination, 67% willing to isolate themselves, 58% willing to wear a face mask, and 48% willing to comply with all three behaviors. Further analysis indicated concern for self and family and higher levels of education were associated with high levels of willingness to comply. Younger people (16–24) were the least willing to comply; especially with wearing a face mask. Those with children reported higher levels of willingness to receive vaccination, and respondents who speak a language other than English at home were less willing to isolate themselves or comply with all behaviors. These findings provide a baseline measure of anticipated public compliance with key public health behaviors in the event of an influenza pandemic in the Australian population, and help to identify groups that may be more resistant to individual measures and may require additional attention in terms of risk communication strategies or health education.Keywords: risk perception, pandemic influenza, compliance, health behaviors